2021
DOI: 10.3389/fendo.2020.599471
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ultrasound-Guided Radiofrequency Ablation as a Treatment Option for Papillary Thyroid Microcarcinoma in the Isthmus: A Retrospective Study

Abstract: BackgroundAbout 3–9.2% of papillary thyroid carcinomas (PTC) are found in the isthmus, which has unique anatomic properties, making treatment more challenging. The aim of this study was to evaluate the treatment and undesirable effects of ultrasound-guided radiofrequency ablation (RFA) for PTC in the isthmus.MethodsThis retrospective case series study assessed 112 patients with single papillary thyroid microcarcinoma in the isthmus, pathologically diagnosed before RFA at the General Hospital of Chinese PLA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…However, whether PTC in the thyroid isthmus is an absolute contraindication to thermal ablation remains unclear. A clinical study enrolled 112 patients with PTC in the isthmus of the thyroid gland to analyze the effect of ablation treatment (82). The results showed that at 18 months after the procedure, the nodules disappeared at a rate of 100% and were even completely absorbed at 1 month after the procedure, although one patient had a recurrence at 7 months after the procedure.…”
Section: Ptc Located In the Isthmus Of The Thyroid Glandmentioning
confidence: 99%
“…However, whether PTC in the thyroid isthmus is an absolute contraindication to thermal ablation remains unclear. A clinical study enrolled 112 patients with PTC in the isthmus of the thyroid gland to analyze the effect of ablation treatment (82). The results showed that at 18 months after the procedure, the nodules disappeared at a rate of 100% and were even completely absorbed at 1 month after the procedure, although one patient had a recurrence at 7 months after the procedure.…”
Section: Ptc Located In the Isthmus Of The Thyroid Glandmentioning
confidence: 99%
“…A total of 41.7% and 95.8% of the nodules subsided within 6 months and 12 months after ablation, respectively, and there was no recurrence or LNM during follow‐up. The team conducted a large sample study in later stages 33,45,46 and confirmed there was no significant difference in recurrence rate, LNM or progression between RFA and surgery in the treatment of PTMC. Patients treated with RFA had shorter hospital stays, blood loss, and residential expenses.…”
Section: Resultsmentioning
confidence: 90%
“…However, an existing study confirmed the effectiveness and safety of ultrasound-guided RFA in the treatment of a single PTMC located in the isthmus. 33 Studies conducted by Yan et al 34,35 suggested that RFA in the treatment of multifocal and bilateral PTMC had similar effectiveness to that of unifocal PTMC, and suggested that RFA could be a promising alternative for patients with multifocal or bilateral PTMC who either refused or were not suitable for surgery.…”
mentioning
confidence: 99%
“…Following the improvement of resolution for ultrasound used in screening, there has been a trend of early and increased discovery for thyroid cancer, including PTCI (15). The lack of clarity regarding the optimal treatment approach has the unfortunate effect of delaying timely intervention.…”
Section: Introductionmentioning
confidence: 99%